A GIS MODELLING APPROACH FOR FLOOD HAZARD ASSESSMENT IN PART OF SURAKARTA CITY, INDONESIA - Tipuk Purwandari; M. Pramono Hadi; Nanette C. Kingma (Indonesian Journal of Geography, 2011)
This research is aimed to assess the flood hazard in part of Surakarta usinghydrodynamic modelling. Flo2D software is used to simulate the flood for 10, 25and 100 year return period. The modeling results include two flood parameters, i.ewater depth and flow velocity. A comparison was made in flood hazard mappingbetween single parameter and multi parameters. The multi parameters hazardmaps improve the reliability of the hazard class delineation. The impact assessmentis done in two point of view, human safety and property damage. The furtherimpact assessment is done by calculating the number of buildings affected by flood.